Groundwater salinization in a subtropical region, Beihai, southern China: Insights from hydrochemistry and multiple isotopes (H, O, S, Sr). (June 2022) - Zhang, Yanpeng; Li, Qinghua; Luo, Yixuan; Yan, Lu; Peng, Kang; Liu, Zimin; Wang, Yanxin
Abstract: Groundwater salinization in coastal aquifers is frequently influenced by seawater intrusion, water-rock interaction, and human activities. We selected the Daguansha high productivity mariculture region and used hydrogeochemical, isotopic analysis methods, coupled with water level and quality monitoring, to identify the main groundwater recharging sources, salinization processes, and evolutionary mechanisms of groundwater in Beihai, China. Our conclusions are based on conventional groundwater chemical components and isotope data for hydrogen, oxygen, sulfur, and strontium. Groundwater levels display notable seasonal variations, and the intensity of anthropogenic exploitation is a major factor influencing fluctuations in groundwater level. The variations of total dissolved solids in groundwater correspond to patterns of spatiotemporal variation in deuterium, sulfur, and strontium isotopes. These results indicate groundwater salinization is influenced by a combination of seawater intrusion and infiltration of water from high-productivity mariculture ponds in the Daguansha area. Notably, interlayer leakage between various aquifers in this area was observed. Local anomalies in groundwater characteristics indicate that groundwater salinization is mainly influenced by water from high-productivity mariculture activities. Investigations of the sources and processes underlying groundwater salinization in the Beihai area can provide a scientific basis for groundwater resource management. Highlights: Hydrochemistry and isotopes were applied to ascertain groundwater salinization. TDS levels correspond to spatiotemporal variations in H, S, and Sr isotope. Integrated seawater intrusion and mariculture activities contribute to groundwater salinization.